International Law against reigning irrationality - Proner, Carol (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
Over the past decade, human rights, activists, representatives of international organisations and scholars of International Law have warned that the international order established in the postwar period is under threat. This work deals with the claim that International Law is currently in crisis by identifying signs of its decline, such as the escalation of armed conflicts and the weakening of multilateralism, and points to the deepening of imbalances of power in the global governance system and the rise of far-right nationalism as the main factors in the current setback. Then, in acknowledgment of international law’s indispensable importance despite its constitutive faults, it looks at alternative paths for the revitalization of multilateralism, emphasizing the role of the Global South in rescuing and improving the modern international order.